Specialization Mapping and Special Talent Sports Class Management (KBIO) - Nugroho, Fajar Adi; Hakim, Abdul Latif Rahman; Septiawan, Dedi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The purpose of this research is to explore the mapping of sports that are in demand among students and to analyze the management of the special talent sports class (KBIO). This research adopts a Mixed Method approach, integrating both qualitative and quantitative research methods to ensure a comprehensive understanding of the topic. Descriptive quantitative methods are used to collect numerical data, such as the number of students enrolling in KBIO over time and their preferred sports disciplines. Meanwhile, descriptive qualitative methods focus on gathering insights from interviews, observations, and document analysis to understand the experiences and perceptions of students, coaches, and school administrators. The sample size consists of seven research samples drawn from schools that have established KBIO programs. The findings of this research reveal a significant increase in the number of prospective students enrolling in special talent sports classes over a two-year period. This upward trend suggests a growing interest among students in specialized sports training and the recognition of KBIO as a valuable program for nurturing sports talent. Furthermore, the research highlights that the management of special talent sports classes has generally met good standards for enhancing sports achievement. Key factors contributing to effective management include well-structured training programs, skilled coaches, adequate sports facilities, and a supportive learning environment. Future research could explore additional factors influencing student participation and the long-term impact of KBIO programs on students' athletic careers